PENGARUH E-SERVICE QUALITY, E-TRUST TERHADAP E- CUSTOMER LOYALTY PADA PENGGUNA LAYANAN KEUANGAN DIGITAL POSPAY DI PT.POS INDONESIA (PERSERO) KCU MANADO - Irene Tesalonika; Efendy Rasjid (MANAJEMEN ADMINISTRASI BISNIS DAN PEMASARAN, 2023)
The rapid development of the scientific and technological revolution in the era of theindustrial revolution 4.0 & 5.0 is currently having an impact on all fields, one of whichhas an impact on the financial services industry. It makes PT. Pos Indonesia as a publicservice facilitator, transformed by launching the digital financial service "Pospay",namely a SOPP network financial payment facility, namely a digital network with fellowpartners, in collaborating on bill payment services. This type of research is quantitativeresearch for research methods using descriptive research methods. In collecting data, themethod used is a questionnaire by taking a sample from one population. The populationtaken is only limited to users of Pospay digital financial services at PT. Pos Indonesia(Persero) KCU Manado, the total population is not known with certainty. while thesamples obtained were 42 samples using the Cochran formula using the non-probabilitysampling method in the form of purposive sampling. The analysis used is descriptivestatistical analysis, total score, classical assumptions, regression analysis and simple andmultiple correlations. While the results of the research analysis, the simultaneouscorrelation coefficient value r = 0.786 indicates that E-Service Quality and E-trust havea strong and significant relationship to increasing E-Customer Loyalty for pospay usersat PT Pos Indonesia (Persero) KCU Manado. The coefficient of determination r2 = 0.618indicates that the increase in E-Customer Loyalty for pospay users at PT Pos Indonesia(Persero) KCU Manado is 61.8% influenced by E-Service Quality and E-trust togetherwhile the remaining 38.2% is influenced by other factors outside of this study. For thisreason, E-Service Quality needs to be improved, of course, supported by a maximumapplication performance system, so that transaction activities are more efficient, safe andcomfortable, that way E-Trust will grow and increase E-Customer Loyalty for Pospayapplication users so that they can achieve company goals.